2008
DOI: 10.1111/j.1745-459x.2008.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Consumer Acceptability of Β‐carotene Rich Sweet Potato Curd

Abstract: Sweet potato (SP) curd prepared by co‐fermenting boiled β ‐carotene rich SP puree, cow's milk with curd culture, was evaluated for consumer acceptability of sensory attributes. One hundred consumers from the Orissa State, India evaluated SP curd in terms of five major sensory attributes, i.e., sweetness, color, texture, aroma and general appearance on a 9‐point hedonic scale. The responses were modeled through binary logistic regression to understand the sensory attributes, which govern the decision process. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…, 2007; Panda et al. , 2009a,b), and their acceptability among consumers has been evaluated (Sivakumar et al. , 2008, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…, 2007; Panda et al. , 2009a,b), and their acceptability among consumers has been evaluated (Sivakumar et al. , 2008, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A study of orange sweet potato curd in adults from rural Orissa, India, demonstrated that color and texture were main drivers of consumer acceptability. 16 In a community-based trial where women and children were given control or zinc-biofortified wheat flour to use at home in Delhi, compliance was high and similar among wheat varieties among women and children. 17 Our research team and collaborators recently conducted an acceptability study in young children in Mumbai where they evaluated recipes prepared with biofortified and control pearl millet and found recipes acceptable, with minor differences noted in consumption or rating of recipes.…”
Section: Discussionmentioning
confidence: 99%
“…Color and texture were found to influence consumer acceptability. The β-carotene supplied by sweet potato enriched yellow color of the curd, and starch and dietary fiber enhanced the thickness of curd (Sivakumar et al, 2008). Similarly, sweet potato curd was prepared using anthocyanin pigments rich sweet potato roots (Panda et al, 2006).…”
Section: Sweet Potato Curd and Yogurtmentioning
confidence: 99%